2007
DOI: 10.1523/jneurosci.2646-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Multisensory Integration in the Ventral Intraparietal Area of the Macaque Monkey

Abstract: The goal of this study was to characterize multisensory interaction patterns in cortical ventral intraparietal area (VIP). We recorded single-unit activity in two alert monkeys during the presentation of visual (drifting gratings) and tactile (low-pressure air puffs) stimuli. One stimulus was always positioned inside the receptive field of the neuron. The other stimulus was defined so as to manipulate the spatial and temporal disparity between the two stimuli. More than 70% of VIP cells showed a significant mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
208
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(245 citation statements)
references
References 47 publications
(113 reference statements)
33
208
4
Order By: Relevance
“…This is similar to what was reported in the primary auditory cortex as electrophysiological recordings suggest that non-auditory events are rather of modulatory influence and do not drive activation at the spiking level, but rather are more evident in post-synaptic potentials . Second, in the superior colliculus or in higher-order multisensory cortical areas of the monkey such as the prefrontal, parietal or inferotemporal areas, the convergence of different sensory modalities is reflected mainly by a modulation (enhancement or depression) of the strength of the sensory responses according to the spatial and temporal congruencies of the two stimuli (Stein, 1998;Avillac et al, 2007;Romanski, 2007). In V1 when presenting a spatially congruent sound, we did not observe an enhancement in visual neuronal activity even at low visual contrast.…”
Section: Electrophysiological Evidence In the Primary Sensory Areascontrasting
confidence: 54%
See 2 more Smart Citations
“…This is similar to what was reported in the primary auditory cortex as electrophysiological recordings suggest that non-auditory events are rather of modulatory influence and do not drive activation at the spiking level, but rather are more evident in post-synaptic potentials . Second, in the superior colliculus or in higher-order multisensory cortical areas of the monkey such as the prefrontal, parietal or inferotemporal areas, the convergence of different sensory modalities is reflected mainly by a modulation (enhancement or depression) of the strength of the sensory responses according to the spatial and temporal congruencies of the two stimuli (Stein, 1998;Avillac et al, 2007;Romanski, 2007). In V1 when presenting a spatially congruent sound, we did not observe an enhancement in visual neuronal activity even at low visual contrast.…”
Section: Electrophysiological Evidence In the Primary Sensory Areascontrasting
confidence: 54%
“…This is particularly the case for the areas buried in the intraparietal sulcus (LIP, VIP) which present anatomical links with cortical areas of different sensory modalities (Lewis and Van Essen, 2000). For instance, in the monkey, the parietal area VIP receives inputs from visual, auditory, somatosensory, vestibular, motor and polysensory areas (Duhamel et al, 1998) that confer typical multimodal responses to the VIP neurons (Bremmer et al, 2002;Schlack et al, 2005;Avillac et al, 2007). Similarly, the connectivity pattern of the LIP Blatt et al, 1990;Lewis and Van Essen, 2000) is consistent with the multisensory properties reported for LIP neurons (Cohen et al, 2005;Russ et al, 2006;Gottlieb, 2007).…”
Section: Heteromodal Connections: Connections Between Different Sensomentioning
confidence: 99%
See 1 more Smart Citation
“…Results showed a larger P300 component over parietal sites evoked by congruent as compared to incongruent visuo-tactile stimulation. Previous single-cell recording studies in monkeys (Avillac et al, 2007;Duhamel et al, 1998;Graziano et al, 2000;Grefkes 20 and Fink, 2005;Iriki et al, 1996) and more recent neuroimaging studies in humans (Gentile et al, 2013(Gentile et al, , 2011Sereno and Huang, 2006) highlighted the presence of multisensory neurons responding to both tactile stimuli and visual stimuli approaching the stimulated site. In particular, recent fMRI studies have identified a set of frontoparietal regions involved in the integration of different bodily-related sensory inputs (Bremmer et al, 2001;Gentile et al, 2011;Makin et al, 2008) and in detecting the conflict between discrepant sources of information (Gentile et al, 2013;Leube et al, 2003).…”
Section: Intracortical Inhibition and Visual Modulation Of Somatosensmentioning
confidence: 99%
“…Neurons in area MST respond to visual and vestibular self-motion signals, and their causal role in heading perception has been confirmed Duffy 1998;Duffy andWurtz 1991a, 1991b;Gu et al 2007Gu et al , 2008Gu et al , 2010Gu et al , 2012Lappe et al 1996;Morgan et al 2008;Page and Duffy 2003;Yu et al 2010). Neurons in area VIP respond not only to visual and vestibular but also to tactile and auditory stimulation (Avillac et al 2005(Avillac et al , 2007Ben Hamed et al 2002;Bremmer et al 2002aBremmer et al , 2002bChen et al 2011b;Duhamel et al 1998;Schlack et al 2002). Like for area MST, behavioral experiments have demonstrated a critical role of area VIP for heading perception (Britten 2008;Chen et al 2013;Zhang et al 2004;Zhang and Britten 2011).…”
mentioning
confidence: 95%